The status of the translation profession in the European Union - Pym, Anthony, 1956-; Grin, François; Sfreddo, Claudio; Chan, Andy L. J. (Anthem Press, An imprint of Wimbledon Publishing Company, 2013)
Based on thorough and extensive research, this book examines in detail traditional status signals in the translation profession. It provides case studies of eight European and non-European countries, with further chapters on sociological and economic modelling, and goes on to identify a number of policy options and make recommendations on rectifying problem areas. There are strong indications that traditional mechanisms of signalling the status of translators are no longer functioning as they should, and that new online mechanisms are turning status into a readily available commodity. Despite demonstrating that some of the traditional status signals do still function relatively well, the book nevertheless finds that others appear to be failing for various reasons, and that this has resulted in a degree of market disorder. Such circumstances may cause good translators to leave the market, which is clearly an undesirable situation for all concerned.